Adaptive Transformations of News Text in the Media (Through Examples of Turkish, Russian and English Articles) - Elvira Rafilovna, Yilmaz (2021)
Informational texts always contain one or more forms of adaptation. The source material is changed according to the standards of the target culture. Adaptation elements can be easily detected by comparing texts in different languages used to reflect a particular news event. The research material of our article is news reports published on the information platforms BBC Turkçe, BBC Russian and BBC World on February-March 2020. Although there are several definitions of the term «adaptation», we adhere to the opinion of scientists, who disclose it in a broad sense. In this approach, the term «adaptation» refers to methods for adapting the original text (as a fragment for displaying objective and social realities) to the socio-cultural conditions of the implicit audience. The message addresser is a participant in this communication process, therefore he should determine the readiness of the implicit reader to accept/ understand/ interpret information. News adapted version is created basing on the perception capabilities. In the comparison of information texts, we also referred to the term «information cores», which means a single information unit of the incident, disclosed within the framework of the main topic.